Permanent Sovereignty over Natural Resources from a Human Rights Perspective: Natural Resources Exploitation and Indigenous Peoples' Rights in the Arctic - Dorothée Cambou; Stefaan Smis (Michigan State University College of Law, 2013)
Article published in the Michigan State International Law Review.